Gut microbial response to host metabolic phenotypes - Hou, Jinliang; Xiang, Jianguo; Li, Deliang; Liu, Xinhua; Pan, Wangcheng (Frontiers in Nutrition, 2022)
A large number of studies have proved that biological metabolic phenotypes exist objectively and are gradually recognized by humans. Gut microbes affect the host's metabolic phenotype, and they directly or indirectly participate in host metabolism, physiology, and immunity through changes in population structure, metabolite differences, signal transduction and gene expression. Obtaining comprehensive information and specific identification factors associated with gut microbiota and host metabolic phenotypes has become the focus of research in the field of gut microbes, and it has become possible to find new and effective ways to prevent or treat host metabolic diseases. This article reviews the content of gut microbes and carbohydrate, amino acid, lipid and nucleic acid metabolic phenotypes, which will help to understand the relationship between gut microbes and host metabolic phenotypes and the current research status.